Influence of rootstocks and pruning times on yield and on nutrient content and extraction in ’Niagara Rosada’ grapevine - Tecchio, Marco Antonio; Moura, Mara Fernandes; Teixeira, Luiz Antonio Junqueira; Pires, Erasmo José Paioli; Leonel, Sarita (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the influence of rootstocks and pruning times on yield and on nutrient content and extraction by pruned branches and harvested bunches of 'Niagara Rosada' grapevine in subtropical climate. The rootstocks 'IAC 766', 'IAC 572', 'IAC 313', 'IAC 571‑6', and '106‑8 Mgt' were evaluated. Treatments consisted of a combination between five rootstocks and three pruning times. At pruning, fresh and dry matter mass of branches were evaluated to estimate biomass accumulation. At harvest, yield was estimated by weighing of bunches per plant. Branches and bunches were sampled at pruning and at harvest, respectively, for nutrient content analysis. Nutrient content and dry matter mass of branches and bunches were used to estimate total nutrient extraction. 'Niagara Rosada' grapevine grafted onto the 'IAC 572' rootstock had the highest yield and dry matter mass of bunches, which were significantly different from the ones observed in 'Niagara Rosada'/'IAC 313'. 'Niagara Rosada' grafted onto the 'IAC 572' rootstock extracted the largest quantity of K, P, Mg, S, Cu, and Fe, differing from 'IAC 313' and 'IAC 766' in K and P extraction, and from '106‑8 Mgt' in Mg and S extraction. Winter pruning results in higher yield, dry matter accumulation by branches, and total nutrient content and extraction.